Holistic Stories of the Whole: Trees and Humans in Richard Powers’ The Overstory - Öztarhan, Esra (Margins/Marges/Margini, 2025)
This paper explores the interplay between human and non-human systems as depicted in Richard Powers' The Overstory. Powers asserts that human and environmental systems are deeply connected and mutually dependent, challenging anthropocentric views that regard nature and non-humans as separate and inferior. Powers reacts to the destruction of nature amidst human interests, seeing trees as marginalized entities within the Anthropocene. The novel is a prime example of an environmental text that effectively problematizes this issue. He portrays trees as significant creatures in humans’ lives. The lives of the trees intricately connect with those of nine human characters and their families, and they affect people’s lives in various ways. The Overstory highlights the interconnectedness and the vital role trees play in human lives. Apart from their significance in human experiences, the novel also celebrates the importance of trees in the ecosystem. The Overstory illustrates human efforts to protect these living entities, emphasizing the common bonds formed through shared struggles against tree decay caused by illness or human impact. Lastly, the novel endows trees with resilience and agency, positioning them as central protagonists. By focusing on specific trees that bind generations and offer refuge, the narrative likens them to humans. They are conscious and intellectual creatures who deserve respect and value. The paper aims to exemplify Powers’ holistic approach to fictionalizing the intrinsic value of trees and portraying them as vital components of the world, rather than marginalizing them as objects.